From Blasthole to Reverse Circulation Sampling – Changing Grade Control Methods at Black Star Open Cut Zinc-Lead Mine, Mount Isa, Queensland - B Young (The Australasian Institute of Mining and Metallurgy, 2011)
Variable bench heights, interaction with underground workings and a steeply dipping orebody are challenges faced daily by geologists at Xstrata Zinc’s Black Star Open Cut (BSOC) Zinc/Lead/Silver mine in Mount Isa, Queensland.BSOC has been in operation since late 2004 and was developed to extract the surface extents of the Zn/Pb/Ag mineralisation mined in the underground lead mine. To date many large scale stopes and extensive development drives have been intersected and successfully mined. The stratigraphically hosted orebodies strike in a north-north westerly direction, dipping ~75° west. Ore production from the pit is currently at 4.5 Mt/a.Historically, sampling was conducted using a multiple spear technique from blasthole cuttings. This method proved to be relatively reliable when blasting benches at a consistent height, but a requirement to vary bench heights to safely collapse and then mine through underground workings reduced sample representivity to unacceptable levels.The purchase and commissioning of a production rig which had been converted for reverse circulation (RC) has allowed for the flexibility of a small rig, with the capacity to easily drill 48 m holes while ensuring sample quality. Sample quality is not the only benefit of introducing RC grade control. By collecting grade control data well in advance, informed decisions can be made by planning, drill and blast and mining departments weeks beforehand, rather than hours before firing. Additionally, seeking operational value to offset higher drilling costs has proved positive with benefits including increased confidence in orebody wireframes, accurate tonnage and grade for proceeding five benches along with the ability to representatively test metallurgical response on a tight grid spacing.